CULTIVANDO MENTES E CONSTRUINDO FUTUROS EM ESCOLAS DE TEMPO INTEGRAL NO MARANHÃO: um estudo sobre as práticas de gestão no Centro Educa Mais Dorilene Silva Castro - CAMARÃO, Felipe Costa (2024)
The research addresses the Management Model of the Full-Time High School Center of the Maranhão State Public Network, with a specific study at the Centro Educa Mais Dorilene Silva Castro. The research started with the following question: how can the systematization of the routines of the management model of the Educa Mais Centers contribute to the qualification of the performance of the management team of the High School units? Based on this question, the general objective was formulated to investigate how the routines of the Centro Educa Mais Dorilene Silva Castro management model can contribute to the qualification of the management team's performance, aiming to prepare an e-book with action proposals for didactic, pedagogical and administrative activities. The dissertation is structured into five sections. In the introduction, we describe the theoretical and methodological configuration of the research. In the second section we present a historical retrospective of the full-time school management model in Brazil and Maranhão. In the third section, we describe some theoretical and methodological concepts of educational and school management. In the fourth section we discuss the empirical part of the research, which was subdivided into the Characterization of the School; Methodological path of the research; Analysis and discussion of research findings; and the proposal for an educational product, which in this case was an E-book with proposed actions for the didactic, pedagogical and administrative activities of the management model of the Educa Mais Centers. The main bibliographic references include: Libâneo (2017), Paro (2018), Lück (2017), Saviani (2019), Cavaliere (2014), Coelho (2013), Moll (2012) and Gadotti (2010). To carry out the empirical part, systematic observation and face-to-face semi-structured interviews were used with the school management trio, in addition to forms applied remotely to the management trio, area/itinerary coordinators, school supervisors (Education Specialists) and the council of leaders . The research concluded that the E-book with proposed actions for didactic, pedagogical and administrative activities could contribute to the performance of full- time school managers.